Decameter pulsar/transient survey of northen sky. First results - Vasylieva, I.Y.; Zakharenko, V.V.; Konovalenko, A.A.; Zarka, P.; Ulyanov, O.M.; Shevtsova, A.I.; Skoryk, A.O. (Радиофизика и радиоастрономия, 2014)
The decameter pulsar/transient survey is now being made using the UTR-2 radio telescope. The survey strategy and parameters, equipment characteristics, data processing algorithms as well as preliminary results are described. The very first result was the discovery of decameter emission of the pulsar J0240+62. Test measurements have shown the sensitivity, reached in the present survey, being 5 Jy for the transient signals, and several mJy – for the periodic pulsar emission.